The Role of Muhammadiyah Organizations for Social Pathology in Makassar City - Risfaisal, Risfaisal; Muslimin, Abdul Azis (Universitas Muhammadiyah Magelang, 2023)
The Industrial Revolution 4.0 in the current era of modernization, has resulted in diverse social impacts, both positive and negative. The negative impacts involve the emergence of various social pathologies or societal issues related to culture. The purpose of this research is to understand the role of the Muhammadiyah Community Organization in addressing the most common social pathological behavioral issues in the city of Makassar. This research uses a qualitative method with a phenomenological approach in Makassar city, involving the leaders of Muhammadiyah branches, Muhammadiyah youth cadres, and the local community as informants. Primary and secondary data are used as types and sources of data. Data collection is conducted through interviews, observations, and documentation. Data analysis involves data reduction, data presentation, and verification, using source triangulation, time triangulation, and technique triangulation to ensure data validity. The research shows that social pathologies continue to occur in the community of Makassar due to the complexity of the heterogeneous society. The Muhammadiyah organization plays a significant role in reducing cases of social pathology in line with their vision and mission as an Islamic movement. This movement also provides ethical, moral, and akhlakul karimah (virtuous character) guidelines in the social order of the community. Therefore, the Muhammadiyah social movement and preaching play a significant role in disseminating modern Islamic teachings that can be accepted by the people and residents of Makassar city.